2021
DOI: 10.1038/s41598-021-88581-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based mortality prediction model for heat-related illness

Abstract: In this study, we aimed to develop and validate a machine learning-based mortality prediction model for hospitalized heat-related illness patients. After 2393 hospitalized patients were extracted from a multicentered heat-related illness registry in Japan, subjects were divided into the training set for development (n = 1516, data from 2014, 2017–2019) and the test set (n = 877, data from 2020) for validation. Twenty-four variables including characteristics of patients, vital signs, and laboratory test data at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Ninan et al reported that a higher J-ERATO score at hospital presentation was an independent predictor of underlying multiple organ dysfunction syndromes, defined as a SOFA score > 2 points ( P < 0.029) 13 . On the one hand, we previously reported the potential of machine learning-based mortality prediction models for heat-related illnesses (AUC, 0.92), using 24 variables at hospital arrival 22 . However, at present, such a model is not clinically feasible in most cases where heat-related illnesses are encountered, as machine learning algorithms require certain computer equipment for calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Ninan et al reported that a higher J-ERATO score at hospital presentation was an independent predictor of underlying multiple organ dysfunction syndromes, defined as a SOFA score > 2 points ( P < 0.029) 13 . On the one hand, we previously reported the potential of machine learning-based mortality prediction models for heat-related illnesses (AUC, 0.92), using 24 variables at hospital arrival 22 . However, at present, such a model is not clinically feasible in most cases where heat-related illnesses are encountered, as machine learning algorithms require certain computer equipment for calculation.…”
Section: Discussionmentioning
confidence: 99%
“…First, Hirano et al [46] used some machine learning algorithm like logistic regression, support vector machine, random forest and XGBoost for mortality prediction for heat-related illness. "Heatstroke study" database in Japan was used in this system for machine learning prediction.…”
Section: Machine Learningmentioning
confidence: 99%
“…Moreover, the Japanese government reported that the number of patients hospitalised owing to cardiovascular diseases will reach twice the 2005 level in 2035, and cardiac and cerebrovascular diseases are estimated to increase 2.15-and 2.05-fold in 2055, respectively 18 . ML techniques can be used to target problems like summer heatstroke 19,20 , although no studies have applied these techniques to the mortality or morbidity risk owing to cardiovascular diseases related to summer weather.…”
Section: Introductionmentioning
confidence: 99%